Drifted Litters of Lake Suwa and Upper Reaches of the Tenryu River - INOUE, Yoshiki; TODA, Hideshige (ENVIRONMENTAL SCIENCE, 2003)
The amount and composition of drifted litters were studied along the all shorelines of Lake Suwa (15 km) from May to October in 1985, and along the upper reaches of the Tenryu River (from Kamaguchi sluice to 11.5 km downstream) from June to November in 1986. Drifted litters collected from the all shorelines of Lake Suwa amounted to 1, 643 kg in air-dry weight, consisting of burnables (43 % by weight) and unburnables (57 %). A large amount of drifted litter was observed on the southeast shoreline. Surface current induced by prominent wind and transport by a large upper river might cause the accumulation of the litters there. Density(weight per unit length of shoreline) of the drifted litters was much higher, in the sandy shorelines than the revetted ones. Drifted litters collected from the upper reaches of the Tenryu River amounted to 1, 398 kg, in which unburnables (74 %) were much abundant than burnables (26 %). There is a significant relationship between the sinuosity of the river and the density of drifted litters. Litter density was high in the non-revetted shoreline. Hydraulic conditions as well as shore substrates might be important factors for settling the litters on the river shoreline.